Portable, and ultrasensitive HR-HPV tests based on nucleic acid biosensors - Ma, Chang; Zou, Minhong; Xu, Ning; Liu, Yan; Wang, Yuru (Frontiers in Cellular and Infection Microbiology, 2024)
Cervical cancer is the third most common cancer threatening women's health globally, and high-risk human papillomavirus (HR-HPV) infection is the main cause of cervical cancer worldwide. Given the recurrent nature of HR-HPV infection, accurate screening is essential for its control. Since the commonly used polymerase chain reaction (PCR) technique is limited by professional equipment and personnel, convenient and ultrasensitive detection methods for HR-HPV are still highly needed.As new molecular detection methods, nucleic acid amplification-based biosensors have the advantages of high sensitivity, rapid operation, and portability, which are helpful for point-of-care testing in rural and remote areas. This review summarized nucleic acid biosensors for HR-HPV screening based on a variety of nucleic acid amplification strategies involved in improved PCR, loop-mediated isothermal amplification, recombinase polymerase amplification, hybridization chain reaction, catalyzed hairpin assembly, and CRISPR/Cas systems. In combination with microfluidic technology, lateral flow assays, electrochemical analysis and other sensing technologies, HR-HPV nucleic acid biosensors have the advantages of high throughput, short response time, high sensitivity and easy operation in the field.Although there are still shortcomings, such as high cost and poor reproducibility, this approach will be suitable for on-site screening of HR-HPV infection or cervical cancer and for auxiliary clinical diagnosis in complex environments and poor areas in the future.